Macroeconomics - Abel (Prentice Hall, 2012)
Abel, Bernanke, and Croushore present macroeconomic theory in a way that prepares readers to analyze real macroeconomic data used by policy makers and researchers. This text uses a unified approach based on a single economics model that provides readers with a clear understanding of macroeconomics and its classical and Keynesian assumptions.